Проявления рудной минерализации в интрузивном комплексе архипелага Аргентинские острова (Западная Антарктика) - Артеменко, Г.В.; Бахмутов, В.Г.; Самборская, И.А.; Кануникова, Л.И. (Мінералогічний журнал, 2011)
В интрузиях габброидов, относящихся к комплексу пород батолита Антарктического п-ова, проявления рудной минерализации магнетита, ильменита и сульфидов связаны с прорывающими их интрамагматическими дайками габбро и более поздними габбро-пегматитами. В них установлены повышенные концентрации V, Co, Cu. В лейкогаббро интрамагматических постинтрузивных даек — более высокое содержание Cu, U, Th, Sc и РЗЭ, а содержание Co в пирите достигает 3,5 %. В интрузиях гранитоидов рудная минерализация пирита, халькопирита и магнетита связана с кварцевыми жилами посттектонической гидротермальной стадии и эпигенетическими процессами в тектонических разломах. В сульфидах из этих проявлений установлены примеси Ag и As. У інтрузіях габроїдів, що належать до комплексу порід батоліту Антарктичного п-іва, прояви рудної мінералізації магнетиту, ільменіту і сульфідів пов’язані з інтрамагматичними дайками габро та більш пізніми габро-пегматитами, що їх проривають. У них встановлений високий вміст V, Co, Cu. У лейкогабро із інтрамагматичних постінтрузивних дайок — значно більший вміст Cu, U, Th, Sc і РЗЕ, а вміст Co в піриті досягає 3,5 %. У інтрузіях гранітоїдів рудна мінералізація піриту, халькопіриту та магнетиту пов’язана з кварцовими жилами посттектонічної гідротермальної стадії та епігенетичними процесами у тектонічних розломах. У сульфідах з цих проявів встановлені домішки Ag і As. In the gabbro intrusions, which belong to the rock complex of the batholith of the Antarctic Peninsula, the mani festations of ore mineralization of magnetite, ilmenite and sulphides are associated with intramagmatic dikes and later gabbro-pegmatites erupting them. V, Co, Cu con centrations are high in them. А significantly higher content of Cu, U, Th, Sc and REE is observed in the gabbro intramagmatic postintrusion dikes, and Co content in pyrite reaches 3.5 %. Ore mineraliztion of pyrite, chalcopyrite and magnetite in the granitoid intrusions is associated with quartz veins of post-tectonic hydrothermal stage and epigenetic processes in the tectonic faults. Ag and As impurities were found in sulfides of these manifestations. Magnetite from the zones of primary ore mineralization is characterized by the presence of impurities Cr₂O₃ and V₂O₅, and ilmenite — MnO. Ore minerals of the zones of superimposed ore mineralization are of different impurity compositions. Ag impurities were detected in pyrite from metasomatites of the Kruls island and As — in pyrite and chalcopyrite in quartz veins on the Barchanes islands. Magnetite is distinguished by the absence of TiO₂, Cr₂O₃, and V₂O₅ impurities.